La poética de la traducción de José María Arguedas: un análisis paratextual (Revista de Crítica Literaria Latinoamericana, 2019)
The present article analyzes a corpus constituted by the totality of the autograph paratexts (prefaces and postfaces) that accompany the translations and the autotranslations that José María Arguedas did from 1938 to 1969. It proposes to investigate Arguedas’s poetics of translation, and to understand his theoretical discourse, his reflections on the method, the motivations, the problems and the translating strategies adopted. Through a paratextual analysis, I will show how Arguedas’s discourse on the translator method does not remain constant, but evolves along his intellectual and literary trajectory, responding to different functions.
Keywords: José María Arguedas; paratext; translation; Peruvian literature